Non-technical skills training in the operating theatre: A meta-analysis of patient outcomes. Issue 4 (August 2019) - Leuschner, Sebastian; Leuschner, Maria; Kropf, Siegfried; Niederbichler, Andreas D.
Abstract: Background: Non-technical skills (NTS) failures have been implicated in a large proportion of surgical errors. The objective of this meta-analysis was to investigate whether NTS training of theatre staff improves patient outcomes. Methods: In a systematic literature search all interventional studies evaluating the effects of NTS training of theatre staff were identified. Primary outcomes included mortality, morbidity, readmission rate and length of hospital stay. Secondary outcomes included staff NTS, checklist use and technical surgical performance. Pooled odds ratios (OR) were determined for event rates and weighted mean differences (WMD) for continuous data. An inverse variance method in a random effects model was used for meta-analysis. Results: A total of 1381 records were identified and nine studies were included. Meta-analysis of mortality was not carried out because only two controlled studies with different study designs were identified. No statistically significant differences were seen in complication rate (5 studies, OR 0.91 [0.73, 1.14]; p = 0.43), readmission rate (3 studies, OR 0.90 [0.63, 1.28], p = 0.56) and length of hospital stay (3 studies, WMD −0.88 days [−2.06, 0.31], p = 0.31) after NTS training. Of the secondary outcomes, an improvement of whole team NOTECHS II scores was observed in the intervention group (3 studies, WMD 6.97 [3.88, 10.06], p < 0.0001). Technical performance and checklist use were unchanged. Conclusions: This meta-analysis failed to find a statistically significant improvement of patient outcomes. These conclusions are based on a small number of heterogeneous studies. Further appropriately powered studies are likely to improve our understanding of the effects of NTS training. Highlights: No statistically significant improvement of patient outcomes was demonstrated after non-technical skills training. A meta-analysis of whole theatre team NTS showed a clinically and statistically significant improvement of whole team NTS. Surgeons' and in most cases anaesthetists' NTS did not improve after training. This meta-analysis is based on a small number of heterogeneous and mostly underpowered studies. Further well-designed studies of NTS training will likely improve our understanding of their impact on patient outcomes.